Pengaruh Biochar dari Berbagai Limbah Organik sebagai Campuran Media Tanam Terhadap Pertumbuhan Vegetatif Bibit Kakao (Theobroma cacao L.) - Sari, Novi Yulanda; Jalil, Abdul (JURNAL GREEN HOUSE, 2025)
Cocoa is one of the leading plantation commodities in Indonesia where more than 95% of the plantation area is managed directly by farmers. The main obstacle faced by cocoa farmers is low productivity due to low fertility of the planting medium in the nursery phase which has an impact on the quality of the cocoa seedlings produced. To solve this problem, innovation is needed in the form of utilizing biochar as an alternative mixture of planting media. This study aims to determine the effect of various types of biochar on the vegetative growth of cocoa seedlings, as well as to identify the most effective type of biochar in supporting increased growth. The study was conducted using a non-factorial randomized block design (RAK) consisting of six treatments and four replications. The treatments given include: bagasse biochar, rice husk biochar, bamboo biochar, corn cob biochar, sawdust biochar, and cocoa skin biochar. Each type of biochar was given as much as 283 grams/polybag and mixed directly into the planting medium with a soil and biochar ratio of 4:1. The results showed that the corn cob biochar treatment had a significant effect on increasing stem diameter, leaf number, leaf length, and leaf width of cocoa seedlings. Thus, corncob biochar is proven to be the most effective type of biochar to support the vegetative growth of cocoa seedlings.